An atomistic view of rigid crystalline supramolecular polymers derived from short amphiphilic, α, β hybrid peptide. Issue 44 (25th October 2022) - Misra, Rajkumar; Netti, Francesca; Koren, Gil; Dan, Yoav; Chakraborty, Priyadarshi; Cohen, Sidney R.; Shimon, Linda J. W.; Beck, Roy; Adler-Abramovich, Lihi
Abstract : The spontaneous self-association of an amphiphilic α, β-hybrid peptide into supramolecular fibers and atomic details of the fibrillar assembly are reported. Abstract : Peptide amphiphiles exhibit excellent self-assembly properties and have potential applications ranging from materials science to nanobiotechnology. Yet, a detailed understanding of supramolecular assembly from an atomistic perspective is still lacking. Here, we demonstrate the spontaneous self-association of an aromatic amphiphilic α, β-hybrid into a hierarchically-oriented crystalline supramolecular polymer under aqueous conditions. Single-crystal analysis after fiber recrystallization revealed that the peptide formed a β-sheet structure stabilized by intermolecular hydrogen bonds and aromatic–aromatic interactions. The head-to-head salt bridge interaction between the opposite charges and hydrogen bonding between the strands account for the elongated shape of the crystal and for the high mechanical strength of the fibers. A new composite biocompatible hydrogel was further fabricated by co-assembly of the hybrid peptide with a well-established hydrogelator. These findings shed light on molecular-level understanding of the supramolecular assembly of hybrid peptide amphiphiles, facilitating development of new composite hydrogels for various applications.